Geochemical characteristics and isotopic reversal of natural gases in eastern Kopeh-Dagh, NE Iran. (December 2016) - Saadati, Hossein; Al-Iessa, Hayder J.; Alizadeh, Bahram; Tarhandeh, Elham; Jazayeri, Mohammad Hasan; Bahrami, Hossein; Rashidi, Mehrab
Abstract: Natural gas samples from two gas fields located in Eastern Kopeh-Dagh area were analyzed for molecular and stable isotope compositions. The gaseous hydrocarbons in both Lower Cretaceous clastic reservoir and Upper Jurassic carbonate reservoir are coal-type gases mainly derived from type III kerogen, however enriched δD values of methane implies presence of type II kerogen related material in the source rock. In comparison Upper Jurassic carbonate reservoir gases show higher dryness coefficient resulted through TSR, while presence of C1 C5 gases in Lower Cretaceous clastic reservoir exhibit no TSR phenomenon. Carbon isotopic values indicate gas to gas cracking and TSR occurrence in the Upper Jurassic carbonate reservoir, as the result of elevated temperature experienced, prior to the following uplifts in last 33–37 million years. The δ 13 C of carbon dioxide and δ 34 S of hydrogen sulfide in Upper Jurassic carbonate reservoir do not primarily reflect TSR, as uplift related carbonate rock dissolution by acidic gases and reaction/precipitation of light H2 S have changed these values severely. Gaseous hydrocarbons in both reservoirs exhibit enrichment in C2 gas member, with the carbonate reservoir having higher values resulted through mixing with highly-mature-completely-reversed shale gases. It is likely that the uplifts have lifted off the pressure on shale gases, therefore facilitated the migration of the gases into overlying horizons. However it appears that the released gases during the first major uplift (33–37 million years ago) have migrated to both reservoirs, while the second migrated gases have only mixed with Upper Jurassic carbonate reservoir gases. The studied data suggesting that economic accumulations of natural gas/shale gases deeper than Upper Jurassic carbonate reservoir would be unlikely. Highlights: All of the gases are thermogenic in origin and the source rock were identified as humic source rocks. Partial reversals in both fields were the result of mixing with high maturity gases. TSR was identified as the major secondary process in Upper Jurassic carbonate reservoir.